2018
DOI: 10.1007/s10456-018-9644-3
|View full text |Cite
|
Sign up to set email alerts
|

The calcium-binding type III repeats domain of thrombospondin-2 binds to fibroblast growth factor 2 (FGF2)

Abstract: Thrombospondin (TSP)-1 and TSP-2 share similar structures and functions, including a remarkable antiangiogenic activity. We have previously demonstrated that a mechanism of the antiangiogenic activity of TSP-1 is the interaction of its type III repeats domain with fibroblast growth factor-2 (FGF2), affecting the growth factor bioavailability and angiogenic activity. Since the type III repeats domain is conserved in TSP-2, this study aimed at investigating whether also TSP-2 retained the ability to interact wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 49 publications
1
24
0
Order By: Relevance
“…Therefore, an urgent need exists for hyperlipemia management. In the present study, we found that resveratrol improved endothelial function through sustaining endothelial cell viability, proliferation, and mobilization (Rusnati et al, 2019). Resveratrol treatment activated HIF1 and AMPK pathways, contributing to Bnip3 upregulation and mitophagy activation.…”
Section: Discussionsupporting
confidence: 59%
“…Therefore, an urgent need exists for hyperlipemia management. In the present study, we found that resveratrol improved endothelial function through sustaining endothelial cell viability, proliferation, and mobilization (Rusnati et al, 2019). Resveratrol treatment activated HIF1 and AMPK pathways, contributing to Bnip3 upregulation and mitophagy activation.…”
Section: Discussionsupporting
confidence: 59%
“…Briefly, we seeded 1 × 10 4 H9C2 cells per well in 96-well plates overnight followed by incubation with LPS for 24 h. Then, after removing the medium, fresh medium supplemented with 0.5 mg/ml MTT (Solarbio) was added and the cells were cultured for another 4 h. The medium was then removed and the formazan product formed in the cells was extracted with 100 μl dimethyl sulfoxide (DMSO; Beyotime; Farber et al, 2018). The absorbance was read at 570 nm using a microplate reader (Enzyme-linked Biotechnology, Shanghai, China) and cell viability in the experimental group was normalized to the control (Rusnati et al, 2019).…”
Section: Mtt Assaymentioning
confidence: 99%
“…Anti-CD47 antibodies and small molecules that mimic the TSP binding site for bFGF are being tested in clinical trials, in preclinical models, or are under development for various diseases. 169,[178][179][180][181][182] Antagonists of these antiangiogenic TSP1 functions have not been tested with antagonists of TSP1's TGF-β activating function. Combined use of a variety of TSP1 functional antagonists could represent a multipronged approach to treating the complex pathogenesis of fibrosis.…”
Section: Tsp1 As a Therapeutic Targetmentioning
confidence: 99%